2-Vertex Covering of a Graph (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we initiate the study on 2-vertex covering of a graph.  We characterize the 2-vertex covering sets in some special graphs, join and corona of two graphs, and we derive some bounds or formulas of the said parameter of each of these graphs.
Keywords: VERTEX COVER; 2-DOMINATION; 2-VERTEX COVERING SET; 2-VERTEX COVER NUMBER